HSPA6: A new autosomal recessive candidate gene for the VATER/VACTERL malformation spectrum. Issue 10 (18th March 2019) - Kause, Franziska; Zhang, Rong; Ludwig, Michael; Schmiedeke, Eberhard; Rissmann, Anke; Thiele, Holger; Altmueller, Janine; Herms, Stefan; Hilger, Alina C.; Hildebrandt, Friedhelm; Reutter, Heiko
Abstract : Background: The VATER/VACTERL association refers to the nonrandom co‐occurrence of at least three of the following component features (CFs): vertebral defects (V), anorectal malformations (ARM) (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). Patients presenting with two CFs have been termed VATER/VACTERL‐like phenotypes. Methods: We surveyed the exome for recessive disease variants in three affected sib‐pairs. Sib‐pair 971 consisted of two brothers with ARM and additional hydronephrosis in one brother. Sib‐pair 1098 consisted of two sisters with ARM. In family 1346, the daughter presented with ARM and additional hypoplasia of both small fingers and ankyloses. Her brother presented with unilateral isolated radial hypoplasia. Sib‐pairs 971 and 1346 resembled a VATER/VACTERL‐like phenotype. Results: We detected a novel maternally inherited missense variant (c.1340G > T) and a rare paternally inherited deletion of the trans‐allele in HSPA6 in both siblings of family 1346. HSPA6 belongs to the heat shock protein (HSP) 70 family. Re‐sequencing of HSPA6 in 167 patients with VATER/VACTERL and VATER/VACTERL‐like phenotypes did not reveal any additional bi‐allelic variants. Conclusions: Until now, only TNF‐receptor associated protein 1 ( TRAP1 ) had been reported as an autosomal recessive disease‐gene for the VATER/VACTERL association. TRAP1 belongs to the heat shock protein 90 family (HSP90). Both Hsp70 and Hsp90 genes have been shown to be important embryonic drivers in the formation of mouse embryonic forelimb tissue. Our results suggest HSPA6 as a new candidate gene in VATER/VACTERL‐like phenotypes.